Leitura semiótica do entendimento de suicídio na cultura Kaiowá-Guarani - Ardenghi, Rodrigo Pael (2009)
This work treats of the lifting from the oral and journalistic records from the cases of suicide from the indian kaiowá / Guarani , located on region from Grande Dourados in Mato Grosso do Sul. The objective of this work is to book and comment analytically the narratives and the journalistic texts that relate the attempts against the life practed by the indians. For that, the maker collect narratives of cases and opinions of natives and comments the culture parts lifted on the observation of the accounts , in addition to piece together and analyze also journalistic materials from the newspaper The Progress that treats the matter. The work picks recover , through narrations and texts of newspaper , the stories and motivations that elevated the taxes of suicides on the villages kaiowá / guarani and they called the attention from the worldwide press. Detailed the influence of the disarticulation from the villages and families , the hybrid culture parts culture and the political positioning from the media. It relates the cultures and traditions inside the aborigine reserve, the rites and the religion , as well as the social organization of the economy , besides data above the etnia suicide. Concludes that these reserves are examples from the croof the culture as an alive and constant transito of two hands, still evidences , the difference between what was related by the own Indians and the way the press interpreted the facts, as soon demonstrating the discrepancies of interpretations of determined suit. The review privileged a covering approach, in order to give voice to different personages on the search by the culture motivations for the hope in the post life